The Impact of CRM on Customer Retention in Baking Sector in Azerbaijan - Akbarova, Ulkar (ADA University, 2022)
In Azerbaijan, especially in the banking sector, there is a lack of research examining the effects of customer relationship management on customer retention. To examine this effect, in this study customer relationship management, customer satisfaction, customer loyalty, and customer retention were selected and tested as variables. In order to measure the CRM, questions aiming to measure the value that the bank gives to the customers were designed and asked to the participants. Customer satisfaction and customer loyalty were also measured in line with the questions given. To calculate customer retention, the averages of the sums of customer satisfaction and customer loyalty were calculated. The study is based on 3 bank customers operating in Azerbaijan and analyzes the effectiveness of customer retention in the management of customer relations in the banking sector of Azerbaijan as a whole. The study was conducted in a virtual environment and the survey results were analyzed using a computer program. The analysis shows that CRM has a positive effect on customer retention . At the same time, we observed that effective CRM has a positive effect on customer satisfaction and loyalty.
Keywords: Customer retention.; Customer satisfaction.; Customer loyalty.; Customer retention -- Banking industry.; Business